2021
DOI: 10.1186/s12887-021-02842-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with bone health status of Malaysian pre-adolescent children in the PREBONE-Kids Study

Abstract: Background Modifiable lifestyle factors and body composition can affect the attainment of peak bone mass during childhood. This study performed a cross-sectional analysis of the determinants of bone health among pre-adolescent (N = 243) Malaysian children with habitually low calcium intakes and vitamin D status in Kuala Lumpur (PREBONE-Kids Study). Methods Body composition, bone mineral density (BMD), and bone mineral content (BMC) at the lumbar sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The variance in body mass on bone accretion if of particular interest because of the beneficial effects of weight-loading on bone accretion. Additionally, muscle contractions generate forces which stimulate bones to adapt their shape and density [33,34]. Prospective studies have shown that lean body mass accretion was the primary determinant of total body peak BMC accretion, explaining 50% of the variability in peak BMC accretion [30].…”
Section: Dependent Variable Effectsmentioning
confidence: 99%
“…The variance in body mass on bone accretion if of particular interest because of the beneficial effects of weight-loading on bone accretion. Additionally, muscle contractions generate forces which stimulate bones to adapt their shape and density [33,34]. Prospective studies have shown that lean body mass accretion was the primary determinant of total body peak BMC accretion, explaining 50% of the variability in peak BMC accretion [30].…”
Section: Dependent Variable Effectsmentioning
confidence: 99%